The sisterhood of the traveling pants / #1. - Brashares, Ann (sisterhood of the traveling pants, 2001)
Carmen decides to discard an old pair of jeans, but Tibby, Lena, and Bridget think they are great and decide that whoever the pants fit best will get them. When the jeans fit everyone perfectly, a sisterhood and a memorable summer begin.